Establishment and application of an SNP molecular identification system for grape cultivars - Fu-qiang WANG; Xiu-cai FAN; Ying ZHANG; Lei SUN; Chong-huai LIU; Jian-fu JIANG (Journal of Integrative Agriculture, 2022)
We aimed to develop a set of single nucleotide polymorphism (SNP) markers that can be used to distinguish the main cultivated grape (Vitis L.) cultivars in China and provide technical support for domestic grape cultivar protection, cultivar registration, and market rights protection. A total of 517 high-quality loci were screened from 4 241 729 SNPs obtained by sequencing 304 grape accessions using specific locus amplified fragment sequencing, of which 442 were successfully designed as Kompetitive Allele Specific PCR (KASP) markers. A set of 27 markers that completely distinguishes 304 sequenced grape accessions was determined by using the program, and 26 effective markers were screened based on 23 representative grape cultivars. Finally, a total of 46 out of 48 KASP markers, including 22 markers selected by the research group in the early stage, were re-screened based on 348 grape accessions. Population structure, principal component, and cluster analyses all showed that the 348 grape accessions were best divided into two populations. In addition, cluster analysis subdivided them into six subpopulations. According to genetic distance, V. labrusca, V. davidii, V. heyneana, and V. amurensis were far from V. vinifera, while V. vinifera×V. labrusca and V. amurensis×V. vinifera were somewhere in between these two groups. Furthermore, a core set of 25 KASP markers could distinguish 95.69% of the 348 grape accessions, and the other 21 markers were used as extended markers. Therefore, SNP molecular markers based on KASP typing technology provide a new way for mapping DNA fingerprints in grape cultivars. With high efficiency and accuracy and low cost, this technology is more competitive than other current identification methods. It also has excellent application prospects in the grape distinctness, uniformity, and stability (DUS) test, as well as in promoting market rights protection in the near future.